A multi-scale analysis of the different interactions between defects and hydrogen: A review on the contribution of the elastic fields. (September 2019) - Hachet, G.; Li, J.; Hallil, A.M.; Metsue, A.; Oudriss, A.; Bouhattate, J.; Feaugas, X.
Highlights: This review of our recent work aims to emphasize the importance of elastic fields of defects on the interactions between hydrogen and crystalline defects. The thermodynamic framework offers an opportunity to lead this reflection. The importance of elastic energy on the solubility, diffusion and segregation of hydrogen as is illustrated. Finally, the origin of the elastic screening is elucidated. Abstract: Hydrogen Embrittlement (HE) is one of the causes mainly evoked in premature rupture of industrial components exposed to an aggressive environment. Many studies have been conducted in order to understand the mechanisms involved during this degradation and the influence of the metallurgical states. Good knowledge of hydrogen interactions with crystal defects is a key element in the understanding of the different damage processes associated with HE in fcc materials. In this state of mind, we have undertaken a systematic study of these interactions in nickel alloys using coupled multi-scale approaches. These latter correspond to the association of atomistic calculations (EAM, DFT) with experimental tests: Electrochemical Permeation (EP), Secondary Ionization Mass Spectrometry (ToF-SIMS) analysis and Thermal Desorption Spectroscopy (TDS) in order to evaluate the hydrogen states in presence of different crystal defects. Among the major results, we focus our attention on the interaction between hydrogen and vacancies in nickel single crystals, the trapping and the segregation of hydrogen for several dislocation distributions (cells, PSB, GBs, …) and the contribution of the grain boundaries (GBs) as well as the precipitates to the hydrogen diffusion and trapping in nanocrystals, polycrystals and bi-crystals. In all the cases, we have questioned the impact of elastic fields associated with the defect to apparent solubility and diffusion of hydrogen. In the second part, we explore the potential impacts of hydrogen on elastic properties and their implication on the mechanisms of plasticity.